Seeing Both Sides / Classic Controversies in Abnormal Psychology - Lilienfeld Scott O. (Brooks/Cole Publishing Company, 1995)
This book gives you the tools to evaluate critically these and other, related questions throughout your life. Preface, Classification and Diagnosis, Is Mental Illness a Myth?, Are Mental Health Professionals Incapable of Distinguishing Abnormality from Normality?, Was DSM-III an Important Advance?, Is the Diagnostic System Biased Against Women?, Psychopathology: Its Characteristics and Causes, Does Schizophrenia Have a Substantial Genetic Component?, Can Anxiety and Depression Be Meaningfully Differentiated?, Does Evidence Support the ''Disease Model'' of Alcoholism?, Is Multiple Personality Disorder a Distinct Syndrome?, Is Borderline Personality Disorder a Diagnosis of Questionable Validity?, Is Sex Reassignment Surgery Ineffective in Improving the Adjustment of Transsexuals?, Is Childhood Depression an Imaginary Entity?, Psychological and Somatic Treatment, Is Psychotherapy Effective?, Is Cognitive-Behavioral Therapy an Important Advance Over Behavior Therapy?, Can Alcoholics Successfully Achieve Controlled Drinking?, Legal and Ethical Issues, Is Mental Illness Unrelated to Violence?, Index.